Centralized wage determination and regional unemployment differences: the case of Italy - Vincenzo Caponi (Institute for the Study of Labor (IZA), 2008)
This paper addresses the problem of the dualism of the Italian economy, particularly of its labor market. Although the Italian labor market is considered to be the most highly regulated among OECD countries, the unemployment rate in the North, which represents two thirds of the whole economy, is one of the lowest in Europe. In contrast, the South faces an unemployment rate between two to five times higher than the North. GDP per capita is also twice in the North than in the South, while nominal wages do not differ substantially across regions. Finally internal migration is the lowest among European countries since the middle seventies. This paper argues that the uniform wage is the result of the centralized wage setting carried on by unions, and that the absence of migration is the result of the proactive role of the government, which in the seventies stopped the mass internal migration from the South to the North and since then is acting to prevent the reappearance of such phenomenon. Uniform wage across regions, the active role of the government to prevent internal mass migration and a structural productivity divide between North and South are the institutional features that, within a general equilibrium matching model, explain the high unemployment rate in the South and, perhaps more interestingly, the low unemployment rate accompanied by low wages in the North even when compared to other western European countries.
urn:nbn:de:101:1-2008072318
Keywords: E24; 330; Italy; European unemployment; internal migration; regional unemployment; Tarifpolitik; Regionale Arbeitslosigkeit; Arbeitsmobilität; Regionaler Arbeitsmarkt; Arbeitsmarkttheorie; Matching; Theorie; Italien